Lean thinking in healthcare services: learning from case studies - Guimarães, Maria Cristina Geraldes Malheiro Machado (2014)
Healthcare organisations, especially in public sector, have been adopting Lean management practices with increasing outcomes’ evidences in several parts of the world, since the beginning of this century. However, Lean deployment in Healthcare services has been addressed in the literature in a surgical way by an array of case reports addressing the “hard” side of Lean deployment, sometimes with no result’s consistency or even follow-up analysis. This thesis seek to add to the operational side of Lean deployment in Healthcare, a complementary understanding of Lean deployment approaches, addressing both “hard” and “soft” sides, identifying the real constraints of Lean in Healthcare sector and the sustainability factors. Supported by two main literature reviews and a multi-case approach, a deep research on the eligible Portuguese cases was conducted answering the questions: (i) What are the different outcomes from Lean deployment in Healthcare?; (ii) What are the barriers to Lean implementation in Healthcare?; (iii) What enables Lean implementation in Healthcare?; (iv) What are the risks of Lean in Healthcare?; (v) How to measure Lean achievements in Healthcare services?; and (vi) How to develop a sustainable Lean culture? This contribution to the academic debate on Lean deployment in Healthcare creates clarity on what can be called Lean practices in Healthcare settings under the light of the concept’s founders; what pattern of a Lean deployment journey was followed by Healthcare organisations; and how different cultural (organisational and national) contexts can influence the pace in pursuing that pattern.